2008
DOI: 10.3354/meps07250
|View full text |Cite
|
Sign up to set email alerts
|

Scales of Mytilus spp. population dynamics: importance of adult displacement and aggregation

Abstract: The control of mussel population dynamics by larval supply and by more local processes affecting post-recruitment survival and growth has received considerable attention. However, immigration and emigration of adults and their contribution to colonization dynamics remain largely unknown. We manipulated the location and density of marked mussels in experimental transplants in the St. Lawrence Estuary (Québec). Our results reveal that colonization by Mytilus spp. is influenced by (1) passive adult movement throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…All mussels (Mytilus spp.) between 2 and 15 mm shell length were considered as recruits (see Petrovic and Guichard 2008), and their abundance in each transplant was also determined in the laboratory to assess mussel recruitment.…”
Section: Community Of Associated Speciesmentioning
confidence: 99%
“…All mussels (Mytilus spp.) between 2 and 15 mm shell length were considered as recruits (see Petrovic and Guichard 2008), and their abundance in each transplant was also determined in the laboratory to assess mussel recruitment.…”
Section: Community Of Associated Speciesmentioning
confidence: 99%
“…For example, spatial patterns, such as self-organised (Liu et al 2012) and fractal structures (e.g. Kostylev and Erlandsson 2001;Erlandsson et al 2005), have important repercussions for mussel bed ecosystems by altering recolonisation (Petrović and Guichard 2008), recruitment (Erlandsson and McQuaid 2004;Commito et al 2014), growth and survival (Petraitis 1995;Liu et al 2013) and resilience (Liu et al 2014) and could not be identified if interactions across the appropriate scales were not examined (Guichard et al 2003;Largaespada et al 2012). Rocky shore mussel beds in South Africa usually exhibit fractal patchy patterns (Erlandsson and McQuaid 2004;Erlandsson et al 2005), and on the south coast of South Africa, these patchy, smallscale patterns are context and density dependent and are probably driven by both local recruitment and behavioural processes (Erlandsson et al 2011;Reaugh-Flower et al 2011), resulting in patterns that influence local population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Marine mussels aggregate into mosaics of patches (mussel beds) over intertidal landscapes. They are exposed to strong disturbances (Paine and Levin 1981) where gaps are created and expanded by the propagation of predator-or wave-induced disturbances (Wootton 2001, Petrovic andGuichard 2008), a process analog to fire propagation in forests. The recovery of mussel beds after disturbance is also spatially aggregated as adults facilitate the recruitment of pelagic larvae and juveniles (Bertness and Grosholz 1985, Petrovic and Guichard 2008, Largaespada et al 2012, Commito et al 2014).…”
Section: The Mussel Bed As a Model Systemmentioning
confidence: 99%
“…Mussel aggregation into large beds alters seabed structure (Palomo et al 2007), reducing water flows (Carrington et al 2008) and increasing sedimentation (Bertness 1984). Through this maturation process, mussel beds form larger areas of aggregated individuals thus increasing their connectedness and structural instabilities by facilitating the onset and propagation of wave disturbances (Guichard et al 2003, Petrovic andGuichard 2008). The resuspension of sequestered matter triggered by the disturbance of entire mussel beds, could drive strong spatial fluxes of matter and affect habitat structure and resource availability.…”
Section: Introductionmentioning
confidence: 99%